RALF/LRX monitor cell wall integrity during tomato fruit formation - Montano, José A; Luna, Ana M.; Doblas, Verónica G (My University, 2022)
Plant developmental processes depend largely on a correct communication between cells, together with the ability to respond to such communication. Traditionally cell to cell communication has been studied through the action of phytohormones such as auxin, ethylene, etc. However, in the past decade, Small Signaling Peptides (SSPs) have been identified as key regulators coordinating an extensive range of developmental and stress processes. Plant cells perceive SSPs at the cell wall by Receptor-Like Kinases (RLKs), activating a huge range of biochemical and physiological processes. SSPs from Rapid Alkalinization Factor (RALFs) family are ubiquitous in dicot plants and they have been associated to cell wall integrity during cell wall remodeling. RALFs peptides can bind two types of receptors: Leucine-Rich Repeat Extensin proteins (LRXs), and Catharanthus roseus RLK1-Like (CrRLK1L). All recent discoveries remark the importance of RALF/LRX/CrRLK1L module regulating cell wall status. A tomato fruit formation is a perfect model to further understand the role of this mechanism, since requires a tightly regulation during the cell wall softening phase. It has already been reported that some members of CrRLK1Ls regulate fruit ripening in few species like tomato, strawberry or apple, remarking the importance of these receptors and their ligands sensing changes produced in the cell wall during the ripening process. Here, we initiate a biochemical and phenotypical characterization of RALF/LRX proteins in order to elucidate their role during tomato ripening process.
Keywords: Tomates - Maduración - Congresos; Péptidos - Congresos; Cell wall; Small peptide; Receptor; Plant molecular biology